ASSESSMENT OF THE BACTERIOLOGICAL QUALITY OF LOCALLY FERMENTED COW MILK (NONO) IN MAIDUGURI, NORTH EASTERN NIGERIA - A. Bello; E. F. Ejeh; F. A. Lawan; A. A. Bitrus (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Contamination of locally fermented cow milk (Nono) by pathogenic bacteria constitute a major public health problem. This was because contaminated milk was a good medium that can support the growth and propagation of microbial pathogens. This study was designed to assess the bacteriological quality of locally fermented cow milk consumed in Maiduguri, northeastern Nigeria. Totally, forty (n = 40) samples of fresh, locally fermented cow milk (Nono) were collected and used in this study. Ten (10) milk samples each were collected from four randomly selected selling points (Monday Market, Custom Market, Kasuwan Shanu and Tashan Bama). The bacteriological quality of each milk sample were analysed using standard procedures for isolation, identification and enumeration of pathogenic bacteria. The mean total plate count ranged from 1.44x10 8 CFU/mL to 10.31x10 8 CFU/mL, while the mean total coliform count range from 0.57x10 8 CFU/mL to 11.17x10 8 CFU/mL. Statistically, there was a significant difference (p<0.05) in the mean total plate count and coliform count of milk samples collected from the four sampling points.Bacteriological culture and biochemical identification of all the isolates revealed Escherichia coli29(72.5%), Klebsiella specie3(7.5%), Salmonella specie 2(5%), Staphylococcus aureus 14(35%) and Streptococcus specie15(37.5%) respectively. All the results were above the acceptable limits (1.0 to 3.0 x 10 5 CFU/mL for total plate count and no coliform count per 100ml of milk sample) set by NAFDAC. Therefore the Nono products consumed in Maiduguri was not safe and wholesome for public consumption. Hence, the need to ensure the maintenance of standard hygienic protocols during the collection, storage, processing and marketing of locally fermented cow milk (Nono) in order to minimize microbial contamination.